A fast and cheap in-house magnetic bead RNA extraction method for COVID-19 diagnosis - Possebon, Fabio Sossai [UNESP] (2022)
COVID-19 has posed a worldwide public health challenge affecting millions of people in different countries. Rapid and efficient detection of SARS-CoV-2 is essential for pandemic control. Reverse Transcription quantitative PCR (RT-qPCR) of nasopharyngeal swabs is the gold standard method for the virus detection, but the high demand for tests has substantially increased the costs and reduced the availability of reagents, including genetic material purification kits. Thus, the present study aimed to compare two bead-based RNA extraction methods (an in-house and a commercial kit) from nasopharyngeal swabs and RT-qPCR detection of SARS-CoV-2. Twenty-five positive and five negative nasopharyngeal swab samples were subjected to extraction of nucleic acids using both methods in an automated platform. Both protocols revealed a high correlation between Cycle Quantifications (Cqs) (r = 0.99, p < 0.0001). In addition, the in-house kit was 89.5 % cheaper when compared to the mean cost of commercial RNA extraction kits. The results show that the in-house protocol is an affordable and reliable option for RNA extraction for SARS-CoV-2 detection from nasopharyngeal swabs.